LIBRARY SERVICES «FACE TO FACE - Rheuskiy, Antonii V.; Kunanec, Nataliia (University Library at a New Stage of Social Communications Development. Conference Proceedings, 2019)
In the article the transformation of individual information services in the context of modern information technology is considered. On the example of Scientific and Technical Library in Lviv Polytechnic National University the complex of services provided in the mode of on-line is highlighted.